Superpowers in a Can: A Visual Journey through Energy Drink Posts on Social Media - Monk, David (Curtin University, 2019)
This research addresses the problem of how energy drink brands such as Red Bull, Monster Energy and V Energy communicate to their target audience of young people aged 18-30 on Instagram and Pinterest. To address this a qualitative netnography was conducted asking 8 participants to choose the images that they find engaging. The results was 138 individual images gathered which was further reconstructed in visual storylines and into brand archetypes to demonstrate the psychological drivers in play when they interpret them.